69 Improving starting time for first operating room (OR) cases in the main OR. (25th October 2019) - Harbi, Bijad; Abdul Aziz, Azrul Azam; Alshengite, Khadija; Ascano, Emann-Jure S; Ansary, Sharifah Bee; Abdullah, Mariam; Rahman, Azura Abdul; Eid, Ahmad Ali; Alam, Kathrina
Abstract : Background: According to the Safety Reporting System (SRS), there is 54% compliance for the first OR cases to start on time. An analysis from the OR Benchmarks Collaborative (ORBC) shows the median for the on-time start for first cases is 64.3%. This study was conducted by a multidisciplinary team involving the Surgery Department and Nursing Services. The study includes patients admitted to the surgical unit for an elective procedure inside the main OR. The aim of the study is to increase the compliance rate for the start time of the first OR cases in the main OR from 54% to 80% by the end of April 2019, by adhering accurately to the OR start time of 0800 h for all cases coming from the surgical ward. Methods: A 5-month retrospective study was done by analyzing the generated SRS for the delayed cases. Upon analysis, six reasons were identified. After which, we utilized a Pareto chart to look at the frequency of occurrence for each reason. The outcome measure is the percentage of compliance to the start time of the first case in the main OR at 0800 h. Process measures include the average time needed for preparing patients for surgery in the surgical unit, average time of bringing the patient to the main OR, average time of nursing hand-over and sign-in of the patient in the holding area, completion of consent, and the average time of on-site arrival of surgeons and anesthesiologists. The balancing measure is OR staff average time working hours. A PDSA (plan-do-study-act) cycle was formulated which focused on the pre-operative team and preparing the patient a day prior to the procedure. The PDSA was tested and implemented for a pilot study of 2 weeks and is currently running on its third month of implementation. Results: After implementation of PDSA, the 2-week pilot study achieved a compliance rate of 89%. The compliance rate for February 2019 is at 97%. Conclusion: The project is largely successful due to continuous and effective monitoring. In the future, we seek to organize a Perioperative Committee that will evaluate the patient flow from ward to OR. Furthermore, we aim to expand the project to other units such as Day Surgery and the Endoscopy Unit, and areas that are sending patients to the OR. Ultimately, the overall conclusions are preventing delays of other scheduled cases, improving patient satisfaction, and improving the utilization of OR time.